The effectiveness of discovery learning-based interactive flipbooks to improve mathematical problem-solving skills - Nika Fetria Trisnawati; Hidayani Hidayani; Erpin Said; Arie Anang Setyo; Yulfince Homba Homba; Qonitah Azzahrah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Problem-solving ability is a crucial competence in mathematics learning, particularly for topics such as exponents and logarithms that are often perceived as abstract and difficult. Limited use of interactive learning media and insufficient opportunities for exploration commonly cause students to struggle in understanding and applying these concepts. This study aims to examine the effectiveness of an interactive flipbook based on discovery learning in improving students’ mathematical problem-solving abilities. A pre-experimental one-group pretest–posttest design was employed involving 28 tenth-grade students. The instruments included observation sheets of learning activities, a student response questionnaire, and learning achievement tests consisting of a pretest and posttest. Data were analyzed using descriptive and inferential statistics, including N-gain analysis. The findings indicate that students’ learning activities improved across meetings, and their responses toward the flipbook and the learning model were positive, with an average score of 3.03. The mean pretest score increased from 19.29 to 67.14 on the posttest, with an N-gain of 0.60 categorized as moderate. Improvements were also observed across problem-solving indicators, particularly in modeling, strategy selection, and concept application. Overall, the interactive flipbook based on discovery learning proved effective in enhancing conceptual understanding and problem-solving skills, making it a valuable digital resource for mathematics instruction. This study contributes empirical evidence on how discovery learning–based interactive flipbooks selectively enhance different indicators of mathematical problem-solving ability, highlighting their stronger impact on problem representation and strategy formulation compared to interpretation and real-world application.